Antibiotic Resistance and Virulence Factors in Clinical Isolates of Stenotrophomonas maltophilia from Hospitalized Patients in Tehran, Iran - Mahrokh Bahrami; Narjess Bostanghadiri; Mehdi Goudarzi; Niloufar Khodaei; Ali Hashemi (International Journal of Microbiology)
Stenotrophomonas maltophilia causes challenging infections in immunocompromised patients, exhibiting increasing resistance to multiple antimicrobials and possessing various virulence genes, including emerging resistance to trimethoprim-sulfamethoxazole. A total of 80 clinical isolates of S. maltophilia were collected from multiple hospitals in Tehran, Iran. This study conducted an analysis of antibiotic susceptibility by disc diffusion method and E-test assay, resistance and virulence gene frequencies were examined by PCR-sequencing, and multilocus sequencing typing (MLST) was performed for strain typing. Across the tested isolates, we observed notably high resistance rates for imipenem 80 (100%), meropenem 78(97.5%), and ceftazidime 72 (90%), while trimethoprim-sulfamethoxazole (SXT) showed a lower resistance rate of 2 (2.5%). Minocycline and levofloxacin demonstrated the highest susceptibility rates, with 70 (87.5%) and 80 (100%), respectively. The prevalence of antibiotic resistance genes blaL1, and blaL2 was 71 (88.75%) and 76 (95%), respectively. Additionally, the PCR analysis revealed that the frequency of virulence genes (fliC, virB, papD, pilU, hlyIII, stmPr1, and stmPr2) was 78 (97.5%), 77 (96.25%), 58 (72.5%), 77 (96.2%), 76 (95%), 31 (38.75%), and 80 (100%), respectively. Resistance to SXT isolate belong to the sequence type (ST15) and exhibits allelic profiles of (10, 29, 21, 21, 32, 32, and 10). The data obtained from our investigation have indicated that SXT remains an efficacious antibiotic and also highlighted the importance of effective management, identification of resistant isolates, and typing methods to address the global prevalence of antibiotic resistance in S. maltophilia.